Development of A Pocketbook of Parental Assistance to Stimulate Early Childhood Physical-Motoric Development in the Digital Age - Yuniarni, Desni (Jurnal Pedagogi dan Pembelajaran, 2025)
The digital age brings new challenges for parents in stimulating early childhood physical motor development. Excessive use of technology can reduce children's physical activity, so an effective mentoring strategy is needed. This study aims to develop a pocket book as a guide for parents in stimulating the physical motor development of early childhood. The research method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection was carried out using interview instruments and questionnaires. The research subjects were parents of PAUD children with material expert validators from PG-PAUD lecturers and media expert validators from PAUD teachers. The analysis techniques used were qualitative and quantitative. The results of the validation test showed that this pocket book has a high level of feasibility based on the assessment of material experts, media experts, and user responses. With this pocket book, it is hoped that parents can be more active in supporting children's physical motor development in the digital era, so that the balance between the use of technology and physical activity can be maintained.